2019
DOI: 10.2106/jbjs.18.01316
|View full text |Cite
|
Sign up to set email alerts
|

Association of Race and Ethnicity with Total Hip Arthroplasty Outcomes in a Universally Insured Population

Abstract: Background: Prior studies have documented racial and ethnic disparities in total hip arthroplasty (THA) outcomes in the U.S. The purpose of this study was to assess whether racial/ethnic disparities in THA outcomes persist in a universally insured population of patients enrolled in an integrated health-care system. Methods: A U.S. health-care system total joint replacement registry was used to identify patients who underwent elective primary THA between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 38 publications
5
37
2
Order By: Relevance
“…Contrary to previous reports, mortality [ [6] , [7] , [8] , [9] , [10] ] and overall rates of 30-day outcomes were comparable between Hispanic and Latino and non-Hispanic white patients. This finding contributes to the ongoing discussion regarding the role of low socioeconomic status or income (frequently more prevalent in Hispanic/Latino populations) as it relates to THA outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to previous reports, mortality [ [6] , [7] , [8] , [9] , [10] ] and overall rates of 30-day outcomes were comparable between Hispanic and Latino and non-Hispanic white patients. This finding contributes to the ongoing discussion regarding the role of low socioeconomic status or income (frequently more prevalent in Hispanic/Latino populations) as it relates to THA outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…The exponential growth in procedure utilization raises the potential for worsened disparities among racial and ethnic minorities who have traditionally experienced lower access to care and worse outcomes for THA [ [3] , [4] , [5] ]. For example, minority patients have been shown to experience increased postoperative pain, prolonged hospitalization, and higher rates of emergency department visits, complications, and mortality [ [6] , [7] , [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, minority patients are more likely to be part of restrictive referral networks and to undergo THA at low-volume hospitals despite living close to high-volume hospitals [25,26]. Given that low-volume hospitals are associated with higher complication rates and poorer outcomes [27], this may further propagate the cycle of distrust and may explain their higher rates of lower postoperative satisfaction [7,13].…”
Section: Discussionmentioning
confidence: 99%
“…Providing culturally appropriate information and services can assist patients in understanding and adhering to treatment options. Improving minority access to care and perioperative optimization holds significant value as studies have shown that in a universally insured and integrated health-care system, minorities have had outcomes similar to or better than whites after undergoing THA [13]. Seeking to improve patients' SDOH is the key of a comprehensive value-based approach to health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation